Trichostatin A Triggers an Embryogenic Transition in Arabidopsis Explants via an Auxin-Related Pathway - Wójcikowska, Barbara; Botor, Malwina; Morończyk, Joanna; Wójcik, Anna Maria; Nodzyński, Tomasz; Karcz, Jagna; Gaj, Małgorzata D. (Frontiers in Plant Science, 2018)
Auxin is an important regulator of plant ontogenies including embryo development and the exogenous application of this phytohormone has been found to be necessary for the induction of the embryogenic response in plant explants that have been cultured in vitro. However, in the present study, we show that treatment of Arabidopsis explants with trichostatin A (TSA), which is a chemical inhibitor of the histone deacetylases, induces somatic embryogenesis (SE) without the exogenous application of auxin. We found that the TSA-treated explants generated somatic embryos that developed efficiently on the adaxial side of the cotyledons, which are the parts of an explant that are involved in auxin-induced SE. A substantial reduction in the activity of histone deacetylase (HDAC) was observed in the TSA-treated explants, thus confirming a histone acetylation-related mechanism of the TSA-promoted embryogenic response. Unexpectedly, the embryogenic effect of TSA was lower on the auxin-supplemented media and this finding further suggests an auxin-related mechanism of TSA-induced SE. Congruently, we found a significantly increased content of indolic compounds, which is indicative of IAA and an enhanced DR5::GUS signal in the TSA-treated explants. In line with these results, two of the YUCCA genes (YUC1 and YUC10), which are involved in auxin biosynthesis, were found to be distinctly up-regulated during TSA-induced SE and their expression was colocalised with the explant sites that are involved in SE. Beside auxin, ROS were extensively accumulated in response to TSA, thereby indicating that a stress-response is involved in TSA-triggered SE. Relevantly, we showed that the genes encoding the transcription factors (TFs) that have a regulatory function in auxin biosynhesis including LEC1, LEC2, BBM and stress responses (MYB118) were highly up-regulated in the TSA-treated explants. Collectively, the results provide several pieces of evidence about the similarities between the molecular pathways of SE induction that are triggered by TSA and 2,4-D that involve the activation of the auxin-responsive TF genes that have a regulatory function in auxin biosynthesis and stress responses. The study infers the involvement of histone acetylation in the auxin-mediated release of the embryogenic programme of development in the somatic cells of Arabidopsis.